The Correlation of Southern Oscillation Index (SOI) with the Rainfall at Rainy and Dry Season Peak in Kintamani-Bangli Region period 1986-2015 - Restitiasih, Wayan Mita; Sukarasa, I Ketut; Andi Yuda, I Wayan (BULETIN FISIKA; Vol 20 No 2 (2019): BULETIN FISIKA, 2019)
A correlation study of the Southern Oscillation Index (SOI) on rainfall at the peak of the wet and dry season in the Kintamani-Bangli region has been carried out by taking SOI values and rainfall data for the period 1986-2015. The rainfall data used were recorded at 2 rain posts, namely Kembangsari and Kintamani. The research aimed to determine the relationship of fluctuations in the value of SOI with the intensity of rainfall, so that it can be used as a regional management plan when El Nino occurs. The method used in this study is correlation. The results obtained from the correlation that is the relationship between SOI value and rainfall in February were quite strong in the Kembangsari post with correlation coefficient of 0.409. Whereas for the Kintamani post the correlation obtained was weak with a correlation coefficient of 0.308. Then in August a weak correlation occurred in the Kembangsari post with a correlation coefficient of 0.2398 and was quite strong in the Kintamani post with a correlation coefficient of 0.4662. So that the influence of El Nino in the Kintamani area in February was more dominant in the Kembangsari post and in August at the Kintamani post.